2021
DOI: 10.1016/j.celrep.2020.108601
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA Desaturase-Mediated Monounsaturated Fatty Acid Availability Supports Humoral Immunity

Abstract: Highlights d B cell activation increases SCD activity and MUFA content d MUFA maintains B cell metabolic fitness and promotes proliferation and class switch d SCD activity is required for anti-viral humoral immunity in vivo d B cell-extrinsic SCD activity can compensate intrinsic B cell SCD loss

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 58 publications
2
37
0
Order By: Relevance
“…Consistent with this, careful titrations allowed identification of a mechanism in which mTORC1 inhibition reduced translation of Aicda mRNA into AID protein in B cells via mTORC1 phosphorylation of eIF4 binding protein (4EBP-1) and eukaryotic (translation) initiation factor (eIF)4E [ 94 ]. A recent work on B cells reported that stearoyl-CoA desaturase, a component of biosynthetic pathways that catalyzes desaturation to generate monounsaturated fatty acids (MUFAs), was downstream of mTORC1 [ 143 ]. Supply of MUFAs was essential for B cells during rapid proliferation, but uptake and utilization of these macromolecules from the interstitial spaces appeared to suffice in the absence of synthesis within the B cells.…”
Section: Blasting Off From the Resting Statementioning
confidence: 99%
“…Consistent with this, careful titrations allowed identification of a mechanism in which mTORC1 inhibition reduced translation of Aicda mRNA into AID protein in B cells via mTORC1 phosphorylation of eIF4 binding protein (4EBP-1) and eukaryotic (translation) initiation factor (eIF)4E [ 94 ]. A recent work on B cells reported that stearoyl-CoA desaturase, a component of biosynthetic pathways that catalyzes desaturation to generate monounsaturated fatty acids (MUFAs), was downstream of mTORC1 [ 143 ]. Supply of MUFAs was essential for B cells during rapid proliferation, but uptake and utilization of these macromolecules from the interstitial spaces appeared to suffice in the absence of synthesis within the B cells.…”
Section: Blasting Off From the Resting Statementioning
confidence: 99%
“…We believe targeting SCD5 is a good strategy to inhibit SCD activity more effectively in the brain and not elsewhere in the body. This is important because of the connection between SCD and MUFAs to proper immune function and other potential negative side effects of broad SCD inhibition ( Meingassner et al, 2013 ; Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stearoyl-CoA desaturase 1 (SCD1) is the rate-limiting enzyme catalyzing the synthesis of MUFAs . Previous studies performed with SCD1 tissue-specific and global knockout mice have shown the essential function of SCD1 in beige fat biogenesis, glucose uptake, and lipid metabolism. , MUFAs generated by SCD1 provide energy in B cells and prevent excessive autophagy and endoplasmic reticulum (ER) stress, indicating the critical function of SCD1 in humoral immunity . Deficiency of SCD1 expression in mice promoted beige adipogenesis, which made this gene a direct target for obesity treatment .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 MUFAs generated by SCD1 provide energy in B cells and prevent excessive autophagy and endoplasmic reticulum (ER) stress, indicating the critical function of SCD1 in humoral immunity. 8 Deficiency of SCD1 expression in mice promoted beige adipogenesis, which made this gene a direct target for obesity treatment. 6 In ruminants, inhibition of SCD1 expression led to decreased synthesis of fatty acids, specifically in bovine adipocytes.…”
Section: ■ Introductionmentioning
confidence: 99%